Muscarinic acetylcholine receptors M2 are upregulated in the atrioventricular nodal tract in horses with a high burden of second-degree atrioventricular block - Nissen, Sarah Dalgas; Saljic, Arnela; Carstensen, Helena; Braunstein, Thomas Hartig; Hesselkilde, Eva Melis; Kjeldsen, Sofie Troest; Hopster-Iversen, Charlotte; D’Souza, Alicia; Jespersen, Thomas; Buhl, Rikke (Frontiers in Cardiovascular Medicine, 2023)
Background: Second-degree atrioventricular (AV) block at rest is very common in horses. The underlying molecular mechanisms are unexplored but commonly attributed to high vagal tone. Aim: To assess whether AV block in horses is due to altered expression of the effectors of vagal signalling in the AV node, with specific emphasis on the muscarinic acetylcholine receptor (M2) and the G protein-gated inwardly rectifying K+ (GIRK4) channel that mediates the cardiac IK,ACh current Method: Eighteen horses with a low burden of second-degree AV block (median 8 block per 20 hours, IQR: 32 per 20 hours) were assigned to the control group, while 17 horses with a high burden of second-degree AV block (median: 408 block per 20 hours, IQR: 1436 per 20 hours) were assigned to the AV block group. Radiotelemetry ECG recordings were performed to assess PR interval and incidence of second-degree AV block at baseline and on pharmacological blockade of the autonomic nervous system (ANS). Wenckebach cycle length was measured by intracardiac pacing (n=16). Furthermore, the expression levels of the M2 receptor and the GIRK4 subunit of the IKACh channel were quantified in biopsies from the right atrium, the AV node and right ventricle using immunohistochemistry and machine learning based automated segmentation analysis (n=9+9). Results: The AV block group had significantly longer PR interval (mean±SD, 0.40±0.05 sec; p<0.001) and longer Wenckebach cycle length (mean±SD, 995±86 ms; p=0.007) at baseline. After blocking the ANS, all second-degree AV blocks were abolished, and the difference in PR interval became absent (p=0.80). The AV block group had significantly higher expression of the M2 receptor (p=0.02), but not the GIRK4 (p=0.25) in the AV node compared to the control group. Both M2 and GIRK4 were highly expressed in the AV node and less expressed in the atria and the ventricles. Conclusion: Here we demonstrate the involvement of the m2R-IK,ACh pathway in underlying second-degree AV block in horses. Expression level of the M2 receptor may be responsible for the high burden of second-degree AV blocks seen in some horses.